Real‐time monitoring of transformer hot‐spot temperature based on nameplate data - Behrooz Rezaeealam; Saeid Askary (IET Generation, Transmission & Distribution, 2023)
Abstract This paper proposes a real‐time hot‐spot monitoring method for three‐phase two‐winding oil‐filled transformers under steady‐state conditions, where the corresponding test certificates are not accessible to the customers. For this purpose, the separate determination of iron‐core and copper losses is achieved by real‐time measuring of voltages and currents in both primary and secondary sides and also employing nameplate data of the transformer, including the winding resistances. Subsequent calculations based on IEEE Std C57.110‐2018 provide the top‐oil and hot‐spot temperatures. It is shown that the estimated top‐oil and winding hot‐spot temperatures and also load and no‐load losses match with the measured ones with the maximum difference of 3.5%, 2%, 2.7%, and 9%, respectively.